A geoarchaeological approach for the localization of the prehistoric harbor of Akrotiri, Thera - Theodōrakopulu, Katerina; Bassiakos, Yannis; Athanassas, Constantin; Schukraft, Gerd; Holzhauer, Ingmar; Hecht, Stefan; Mächtle, Bertil; Wagner, Günther A. (Digital geoarchaeology, 2018)
The disastrous volcanic eruption of Thera in the Aegean that happened in late seventeenth century BC (Late Bronce Age, LBA) buried under a thick mantle of volcanic ash the thriving city harbor of Akrotiri, situated at the southern edge of the island. The archaeological excavations at the site have witnessed the city’s wealth and flourish; numerous, luxurious, and outlandish finds clearly indicate well-established maritime contacts between Akrotiri and eastern Mediterranean lands. Such maritime operations and overseas trade required, apparently, adequate harbor facilities. This paper deals with geoarchaeological and geophysical studies aiming at the localization of the buried harbor, a so far unrealized ambitious aim, in spite of the repeated intense attempts undertaken in the last decades. Preference for the relevant investigation was given to three small littoral valleys situated in small distances at both sides of the settlement, suggesting shallow bays before the Minoan eruption, hence probably having hosted the searched harbor(s). Prior to the fieldwork undertaken, all available geological and other related data were cartographically outlaid by means of GIS. Afterwards, in situ geomorphologic studies were conducted, followed by one littoral drilling and geophysical investigations including seismic refraction and electrical resistivity tomography (ERT). Both geophysics and drilling have shown that the hard pre-Minoan basement (consisting of dense andesitic lavas) is situated at depths of ca. 25 m in the Mavrorachidi valley.